Authentic and posed emotional vocalizations trigger distinct facial responses. (August 2021) - Lima, César F.; Arriaga, Patrícia; Anikin, Andrey; Pires, Ana Rita; Frade, Sofia; Neves, Leonor; Scott, Sophie K.
Abstract: The ability to recognize the emotions of others is a crucial skill. In the visual modality, sensorimotor mechanisms provide an important route for emotion recognition. Perceiving facial expressions often evokes activity in facial muscles and in motor and somatosensory systems, and this activity relates to performance in emotion tasks. It remains unclear whether and how similar mechanisms extend to audition. Here we examined facial electromyographic and electrodermal responses to nonverbal vocalizations that varied in emotional authenticity. Participants ( N = 100) passively listened to laughs and cries that could reflect an authentic or a posed emotion. Bayesian mixed models indicated that listening to laughter evoked stronger facial responses than listening to crying. These responses were sensitive to emotional authenticity. Authentic laughs evoked more activity than posed laughs in the zygomaticus and orbicularis, muscles typically associated with positive affect. We also found that activity in the orbicularis and corrugator related to subjective evaluations in a subsequent authenticity perception task. Stronger responses in the orbicularis predicted higher perceived laughter authenticity. Stronger responses in the corrugator, a muscle associated with negative affect, predicted lower perceived laughter authenticity. Moreover, authentic laughs elicited stronger skin conductance responses than posed laughs. This arousal effect did not predict task performance, however. For crying, physiological responses were not associated with authenticity judgments. Altogether, these findings indicate that emotional authenticity affects peripheral nervous system responses to vocalizations. They also point to a role of sensorimotor mechanisms in the evaluation of authenticity in the auditory modality.